Titik Lelah Peradaban dalam Dinamika Oligarki: Tinjauan Sosiologis dan Eskatologis (Studi Geopolitik Perang Amerika Serikat-Israel vs Iran) - Qomarullah, Muhammad; Muklis; Febriansyah, Irlan (Hutanasyah : Jurnal Hukum Tata Negara, 2026)
This research report presents an in-depth analysis of the phenomenon of civilization's tipping point triggered by the increase in unsustainable socio-political complexity, the dominance of oligarchic businesses in modern democratic structures, and the normalization of wealth accumulation without a productive process (rent-seeking). This study aims to analyze the phenomenon of "civilization fatigue points" represented through the escalation of the conflict between the US-Israel axis and Iran. Using a qualitative-descriptive approach, this study dissects these geopolitical tensions from two main points of view: political sociology and transcendental eschatology. The results of the analysis show that civilization is currently in a phase of diminishing marginal returns, where every attempt to solve the problem through increased bureaucracy and technology actually increases energy and social costs per capita. Sociologically, this condition is exacerbated by the tremendous concentration of material wealth in the hands of a handful of elites (oligarchs) who utilize state instruments for the defense of wealth rather than public welfare. The case study of Iran vs US-Israel is a microcosm of the fragility of the contemporary world system which is on the verge of a major transformation, both in terms of political materiality and spirituality of the times.